Xinnao Shutong Modulates the Neuronal Plasticity Through Regulation of Microglia/Macrophage Polarization Following Chronic Cerebral Hypoperfusion in Rats - Wang, Liye; Wang, Rongliang; Chen, Zhigang; Zhao, Haiping; Luo, Yumin (Frontiers in Physiology, 2018)
Xinnao shutong (XNST) capsules have been clinically used in China to treat cerebrovascular diseases. Previous studies have demonstrated that XNST has significant neuroprotective effects against acute cerebral ischemic stroke. The present study investigated the effects and mechanisms of XNST treatment following chronic cerebral hypoperfusion. Thirty-six adult male Sprague-Dawley rats were treated with XNST or vehicle following permanent bilateral common carotid artery (BCCA) ligation. Body weight was recorded on days 0, 3, 7, 14, 28, and 42 post-surgery. The Morris water maze test was used to assess cognitive function in rats. Immunofluorescent staining and western blot were used to assess the severity of neuronal plasticity, white matter injury, and the numbers and/or phenotypic changes incurred to microglia. Protein levels of p-AKT (Thr308) and p-ERK (Thr202/Tyr204) were detected 42 days after BCCA ligation was performed. The results indicate that XNST treatment significantly reduced escape latency, decreased the frequency of platform crossing compared to the vehicle group. Synaptophysin, protein levels improved and white matter injury ameliorated following XNST treatment. Meanwhile, XNST reduced the number of M1 microglia and increased the number of M2 microglia. Furthermore, p-AKT (Thr308) and p-ERK (Thr202/Tyr204) levels were increased 42 days following BCCA ligation. In summary, our results suggest that XNST mitigates memory impairments by restoration of neuronal plasticity and by modulation of microglial polarization following chronic cerebral hypoperfusion in rats.